Association between Clinical Characteristics of Pregnant Women in the Third Trimester and Low Back Pain - Dewi, Mira Dyani; Rachmawati, Meike (Global Medical & Health Communication (GMHC), 2024)
Pregnancy is a physiological condition characterized by growth in both the fetus and the mother. Various biomechanical, physiological, and structural changes in pregnant women cause body posture changes, impacting low back pain (LBP). In the third trimester, LBP pain felt by pregnant women is usually accompanied by activity limitations and a decreased quality of life. This study aimed to determine the association between the clinical characteristics of pregnant women in the third trimester and low back pain. This research was conducted at the Department of Obstetrics and Gynecology and Department of Physical Medicine and Rehabilitation, Faculty of Medicine, Universitas Padjadjaran/Dr. Hasan Sadikin General Hospital, Bandung from June to December 2017. The method is observational analysis with a cross-sectional approach with a sample of pregnant women in their third trimester who complained of lower back pain and lived in Bandung. According to the findings, the majority of pregnant women with LBP in the third trimester were under the age of 35 (33 of 38), had multiparous parity (25 of 38), had normal pre-pregnancy weight (21 of 38), gained an average of 11.28 kg during pregnancy, and had a median pain intensity of 5. Age was the only factor significantly correlated with LBP pain intensity; parity and weight gain during pregnancy did not. The study concludes a significant association between age in the third trimester of pregnancy and the intensity of LBP pain. Still, no significant association was found between parity and weight gain during pregnancy with the intensity of LBP pain.